2010
DOI: 10.1017/s095026881000110x
|View full text |Cite
|
Sign up to set email alerts
|

Marching cohort ofHelicobacter pyloriinfection over two decades (1988–2007): combined effects of secular trend and population migration

Abstract: The prevalence of Helicobacter pylori infection is decreasing in developed countries. In this study we included 22,612 patients in whom a first culture of gastric biopsy (routinely performed in our medical centres) yielded an interpretable result over a 20-year period (1988-2007) in Brussels. The effects of patients' age, gender and ethnic background were analysed. The overall proportion of H. pylori-infected patients was 37·7%, with a progressive decline over time (P<10(-5)). A gender effect was observed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
5
18
2
Order By: Relevance
“…The latter may contribute, as our data suggest continuing acquisition of H. pylori at least until the age of 7, consistent in children of Dutch and non-Dutch ethnicities. The higher H. pylori prevalence in children of non-Dutch ethnicity confirms findings of other studies [27, 28]. When comparing previous studies, the exact colonization rate of particular ethnic groups may differ due to differences in age or selected populations, but nevertheless it is clear that subjects of non-Western ethnicity comprise risk groups for H. pylori colonization within multi-ethnic populations of Western cities.…”
Section: Discussionsupporting
confidence: 85%
“…The latter may contribute, as our data suggest continuing acquisition of H. pylori at least until the age of 7, consistent in children of Dutch and non-Dutch ethnicities. The higher H. pylori prevalence in children of non-Dutch ethnicity confirms findings of other studies [27, 28]. When comparing previous studies, the exact colonization rate of particular ethnic groups may differ due to differences in age or selected populations, but nevertheless it is clear that subjects of non-Western ethnicity comprise risk groups for H. pylori colonization within multi-ethnic populations of Western cities.…”
Section: Discussionsupporting
confidence: 85%
“…The observed H. pylori colonization rate in the Dutch study subjects was consistent with a previous study in subjects of the same age . Studies evaluating H. pylori colonization in immigrant groups all showed higher infection prevalence than in native populations . A previous study of 288 adults in Rotterdam showed nearly similar positivity rates among different immigrant groups, however, higher prevalence in subjects of Dutch origin (46%) than we observed .…”
Section: Discussioncontrasting
confidence: 57%
“…Treatment with macrolides induces point mutations in the 23S rRNA gene that could result in the acquisition of resistance (41). Despite the heterogeneity of our population (33), mutations involved in CLR r were comparable to mutations reported previously by other studies in Europe, which were mainly A2142G/43G mutations and various combinations of the wild type as well as point mutations related to the presence of multiple isolates (mixed population) in the same biopsy specimen (1,12,31,37,43,44,49). In contrast with data from many previous studies (1,2,11,24), our study identified the A2142C mutation in some strains from children, probably due to the large number of isolates in our study.…”
Section: Vol 49 2011 Two-decade Survey Of H Pylori Resistance In Bmentioning
confidence: 94%
“…Samples from children were collected at the Queen Fabiola Children's University Hospital and at the Saint-Pierre University Hospital, while samples from adults were collected at the CHIREC/site de la Basilique, at the Brugmann University Hospital, and at the Saint-Pierre University Hospital, as previously described (33). Other invasive tests for H. pylori detection were also performed during upper GI endoscopy (histology and rapid urease tests).…”
Section: Methodsmentioning
confidence: 99%